2022
DOI: 10.1029/2021ms002765
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Improving Numerical Weather Prediction of Heavy Rainfall

Abstract: Modeling and predicting rainfall, and in particular heavy rainfall events, remains is challenging. The relevant multi-scale dynamics range from small-scale droplet interactions to large-scale weather systems. Further, the high intermittency in space and time, as well the strongly non-Gaussian, right-skewed distribution (Koutsoyiannis, 2004a(Koutsoyiannis, , 2004b) make accurate predictions difficult.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 55 publications
(70 reference statements)
4
19
0
Order By: Relevance
“…In general, most of the analyzed DL were able to reproduce reasonably well the occurrence of precipitation events. However, we found that the U-Net outperformed the rest of the tested architectures by a large margin, which is in line with previous studies (Hess & Boers, 2022;Larraondo et al, 2019) that used a U-Net architecture to simulate precipitation. In general, the skill scores that measure the precision to classify heavy precipitation events (i.e., >95th percentile) were higher than those obtained for extreme precipitation events (i.e., >99th percentile), due to the unbalanced number of classes where the number of extremes is significantly reduced in the training data.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In general, most of the analyzed DL were able to reproduce reasonably well the occurrence of precipitation events. However, we found that the U-Net outperformed the rest of the tested architectures by a large margin, which is in line with previous studies (Hess & Boers, 2022;Larraondo et al, 2019) that used a U-Net architecture to simulate precipitation. In general, the skill scores that measure the precision to classify heavy precipitation events (i.e., >95th percentile) were higher than those obtained for extreme precipitation events (i.e., >99th percentile), due to the unbalanced number of classes where the number of extremes is significantly reduced in the training data.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, many studies have proposed using sophisticated ML methods to improve precipitation estimates in various contexts, such as precipitation nowcasting (Ayzel et al, 2019) and post-processing of NWP precipitation output (Hess & Boers, 2022). This section reviews the most relevant studies closely related to our objectives and methodology.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This changes the flavor of the problem substantially—for example, both papers prioritize standard metrics like RMSE, which is inappropriate on higher resolutions and shorter timescales (Rossa et al., 2008 ). Hess and Boers ( 2022 ) uses independent data sets, and has a particular focus on heavy rainfall events, but does not increase resolution. Finally, many authors have used convolutional neural networks for nowcasting: forecasting precipitation events over short lead times (typically 0–6 hr).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, UNet uses multiple convolutions and deconvolutions to fuse multiscale features. UNet has been used for correction of numerical forecast products and precipitation forecast (Grönquist, et al., 2021; Han et al., 2021; Hess & Boers, 2022), and it is representative enough as a benchmark model. GIPMN single and UNet used the predictors in both Table 1 (a and b) as inputs.…”
Section: Resultsmentioning
confidence: 99%